2017
DOI: 10.1021/acs.chemmater.6b04135
|View full text |Cite
|
Sign up to set email alerts
|

AgBiI4 as a Lead-Free Solar Absorber with Potential Application in Photovoltaics

Abstract: AgBiI4 powder, crystals, and polycrystalline films were synthesized by sealed tube solid state reactions, chemical vapor transport (CVT), and solution processing, respectively, and their structural, optical and electronic properties are reported. The structure of AgBiI4 is based unambiguously upon a cubic close packed iodide sublattice, but it presents an unusual crystallographic problem: we show that the reported structure, a cubic defect-spinel, cannot be distinguished from a metrically cubic layered structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
176
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(206 citation statements)
references
References 67 publications
16
176
0
Order By: Relevance
“…Moreover, BiI 3 shows promising efficiency in solar cells and other bismuth‐halide materials show interesting properties that may be useful in solar cells . A screening of different Ag 1‐3 x Bi 1+ x I4 (0< x <0.19) compounds has previously been performed, indicating that there exist several stable compositions and the structure is not trivial owing to the vacancies in the system …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, BiI 3 shows promising efficiency in solar cells and other bismuth‐halide materials show interesting properties that may be useful in solar cells . A screening of different Ag 1‐3 x Bi 1+ x I4 (0< x <0.19) compounds has previously been performed, indicating that there exist several stable compositions and the structure is not trivial owing to the vacancies in the system …”
Section: Figurementioning
confidence: 99%
“…[29] As creening of different Ag 1-3x Bi 1 + x I4 (0 < x < 0.19) compounds has previously been performed, indicating that there exist several stable compositions and the structure is not trivial owing to the vacancies in the system. [30] Here, solutions with am ixture of silver iodide (AgI) and bismuth iodide (BiI 3 )w ith molar ratio of AgI/BiI 3 = 2:1a nd AgI/ BiI 3 = 1:2w ere used to synthesize materials with differentc rystal structures. These materials were used in as olar cell between TiO 2 ,w hich acts as electron-conducting layer,a nd poly(3-hexylthiophene-2,5-diyl) (P3HT), whichi su sed as holetransportl ayer.T he PCE of the best devices was above 2% under 1000 Wm À2 (1 sun), AM 1.5 Gs imulateds olar illumination.…”
mentioning
confidence: 99%
“…Recently,S ansom et al [30] investigated the structure of AgBiI 4 by using single crystal X-ray diffraction (SCXRD) and powder Xray diffraction (PXRD)a nd found that although the structure of AgBiI 4 is based unambiguously upon ac ubic-close-packed iodide sublattice, the cation sublattice can adopt either ac ubic-defect-spinel structure, in whicha ll tetrahedral sites are empty (i.e.,t he rudorffite structure according to the NaVO 2 prototype), or am etrically cubic-layered structure analogues to CdCl 2 .…”
mentioning
confidence: 99%
“…O In contrast to tin-based and binary cation perovskite, antimony and bismuth-based perovskite-like materials are highly stable in ambient atmosphere and possess exceptional optoelectronic properties 25 . These have recently been used as a lead-free absorber in PSCs [25][26][27][28][29][30] . To some extent, antimony shares the less sharp onset of absorption as the tin-based systems.…”
mentioning
confidence: 99%